Schwannoma of Ulnar Nerve. About a Case and Literature Rev - PADONOU, ABIODOUN; ALIHONOU, THIERRY; LAWSON, ERIC; CHIGBLO, SÈGLA PASCAL ERIC; HANS M, ARISTOTE (My University, 2017)
Schwannoma is one of the tumors isolated from the peripheral nerves, developing at the expense of Schwann cells of the nerve sheath. Rare and generally benign, the lesion sits preferentially in the upper limb, especially at the extension surfaces of joints. We report here the case of a 31-year-old patient who consults for a swelling of the medial aspect of the left elbow, appeared about 5 years ago, initially painless but gradually became very sensitive. Standard radiography was strictly normal and the ultrasound evoked lipomatous swelling. Surgical excision was performed and anatomopathological examination of the surgical specimen concluded Schwannoma. Post-surgery follow-ups were satisfactory, with a disappearance of symptoms at 12 months of follow-up.
Keywords: Schwannoma; Nerve Tumor; Ulnar Nerve